Developing Intercultural Communicative Competence in Local ELT - Beresova, Jana (Berlin : Peter Lang GmbH, 2019)
Language and culture relate to each other. It is important to refine teaching processes to enable language learners to use target languages effectively. This book shows that language and culture should be viewed in their interrelationship as they have a significant impact on the naturalness and appropriateness of discourse.
Cultural awareness - Intercultural communicative competence - National language curricula - Teacher training
Off-Campus Access:User ID and Password Required
On-Campus Access: User ID and Password Required
Access type: Non-expiring Rental
ENH
Mode of access: Internet
VitalSource
Task Force Research Grant
Keywords: Foreign Language Study; English as a Second Language; English language; Electronic books